Pengaruh Bermain Playdough terhadap Kemampuan Motorik Halus Anak Usia 4-5 Tahun di TK Swasta Kristen Kalam Kudus 2 Medan - Panni Ance Lumbantobing; Hilma Mithalia Shalihat; Dian Sastra Dao (Journal on Education, 2023)
The purpose of this study was to determine the effect of playing playdough on fine motor skills of children aged 4-5 years at Kalam Kudus 2 Private Christian Kindergarten, Medan. The sample in this study was children grade A class GOODNESS totaling 18 children. This research was Experimental research with Pre-experimental One Group Pretest and Posttest Design. The sampling technique used was the Total Sampling technique. Data collection technique is by using observation and documentation. The data from this study were analyzed statistically by using SPSS 22 with the formula mean, median, mode, normality test Kolmogrov-Smirnov one sample t-test. Based on the results of the study, it was found that the fine motor skills of children in the pretest obtained an average of 8.28 with a percentage of 72%, while after the treatment or posttest it increased with an average score of 12.5 with a percentage of 56%. Based on the hypothesis test, the results of the one sample t-test analysis show that if t count > t table then Ha is accepted (value 22,493 > 2,109) and a significant value of 0.35 > 0.05. In accordance with the criteria, if t count > t table, Ha is accepted and Ho is rejected, which means that there is an effect of playing playdough on the fine motor skills of children aged 4-5 years at the Kalam Kudus 2 Private Christian Kindergarten, Medan.